2010
DOI: 10.1080/01488371003697939
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Coping and Self-Forgiveness After the Death of a Care-Receiver

Abstract: This study explores the relationship of self-forgiveness with adaptive coping and nonadaptive coping. This study addresses self-forgiveness as part of the grieving process of Alzheimer's disease caregivers. One hundred and thirty-three caregivers who had recently lost a loved one were surveyed. The bivariate analysis revealed a significant relationship between self-forgiveness and adaptive coping and non-adaptive coping. Furthermore, stepwise regression models computed for the study variables revealed that ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…The correlation between grief and forgiveness in bereaved mothers was significant. This finding is consistent with the results of previous studies focusing on different populations (Currier et al., 2013; Jacinto, 2010). From the forgiveness subscales, we found the relationship between grief and forgiveness toward God was significant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The correlation between grief and forgiveness in bereaved mothers was significant. This finding is consistent with the results of previous studies focusing on different populations (Currier et al., 2013; Jacinto, 2010). From the forgiveness subscales, we found the relationship between grief and forgiveness toward God was significant.…”
Section: Discussionsupporting
confidence: 93%
“…We were intrigued by the finding that even mothers who indicated their religious affiliation was “no religion” in the demographic survey identified God as an agent who hurt them in the context of the loss. The relationship of grief and self-forgiveness was also significant, similar to previous research (Jacinto, 2010). These findings suggest that forgiveness therapy might help bereaved mothers cope with the loss of their children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, a great deal of empirical research appears to substantiate this optimistic understanding of self‐forgiveness. For instance, Jacinto () demonstrated that self‐forgiveness among caregivers reduced levels of guilt and improved self‐perceptions, following the death of the person in their charge. The ability to self‐forgive is also positively related to feelings of self‐worth in couples that have recently separated and are adjusting to divorce (Rohde‐Brown & Rudestam, ).…”
Section: The Meaning Of Self‐forgivenessmentioning
confidence: 99%
“…Researchers have also found that ways of responding to stressful situations are associated with self-forgiveness at the dispositional and situational level. For example, caregivers whose care-receiver recently died were more likely to forgive themselves for past regrets associated with caretaking when they utilized adaptive coping strategies, such as seeking emotional support, accepting oneself, and positively reframing experiences (Jacinto, 2010). Dispositional selfforgiveness was found to be positively correlated with ability to engage in emotion repair and with attention to and clarity of one's emotions; in path analysis of that data, however, emotional clarity was the primary predictor of self-forgivingness (Hodgson & Wertheim, 2007).…”
Section: Self-forgiveness and Wellbeingmentioning
confidence: 99%